ANALYSIS OF THE CURRENT STATE AND POTENTIAL OF THE USE OF TOURIST RESOURCES IN SAMARKAND REGION (International Conference on Medical Science, Medicine and Public Health, 2025)
Tourism has become a major driver of global economic growth, with countries and regions increasingly relying on their natural, cultural, and historical assets to attract international visitors. Samarkand, one of Uzbekistan’s most prominent cities, is strategically positioned as a key destination along the ancient Silk Road, a crossroads of civilizations with a rich historical legacy that spans thousands of years. Known for its magnificent monuments, architectural masterpieces, and cultural depth, Samarkand has long been a focal point for travelers, scholars, and historians alike. However, the true potential of the region’s tourism resources remains largely untapped, offering a wealth of opportunities for growth and development. Samarkand is home to several UNESCO World Heritage sites, including the Registan Square, the Shah-i-Zinda necropolis, Bibi-Khanym Mosque, and the Ulugh Beg Observatory. These historical landmarks not only reflect the region's profound architectural and cultural significance but also underscore its historical role as a melting pot of diverse cultures, ideas, and knowledge. As one of Central Asia's most historically rich regions, Samarkand offers unique potential for attracting tourists who are drawn to its fusion of ancient history, vibrant culture, and contemporary offerings.